2019
DOI: 10.3389/fnsys.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

Sleep–Wake Cycle in Young and Older Mice

Abstract: Sleep plays a key role in multiple cognitive functions and sleep pattern changes with aging. Human studies revealed that aging decreases sleep efficiency and reduces the total sleep time, the time spent in slow-wave sleep (SWS), and the delta power (1–4 Hz) during sleep; however, some studies of sleep and aging in mice reported opposing results. The aim of our work is to estimate how features of sleep–wake state in mice during aging could correspond to age-dependent changes observed in human. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
70
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 58 publications
15
70
4
Order By: Relevance
“…On the other hand, aging mice also exhibit similarities to aging humans. For example, aged mice exhibit increases in sleep fragmentation, increases in sleep duration during active phase of sleep-wake cycle (light for humans, dark for mice), and decreased REM sleep at the end of quiet phase of sleep-wake cycle (Soltani et al, 2019). Thus use of mouse models should be considered with caution when modeling human condition.…”
Section: Swa Disruptions In Mouse Models Of Admentioning
confidence: 99%
“…On the other hand, aging mice also exhibit similarities to aging humans. For example, aged mice exhibit increases in sleep fragmentation, increases in sleep duration during active phase of sleep-wake cycle (light for humans, dark for mice), and decreased REM sleep at the end of quiet phase of sleep-wake cycle (Soltani et al, 2019). Thus use of mouse models should be considered with caution when modeling human condition.…”
Section: Swa Disruptions In Mouse Models Of Admentioning
confidence: 99%
“…Sleep patterns change with ageing 27 . Animal studies have revealed that aged mice sleep more than young‐adult mice during the dark phase, and that sleep fragmentation and sleep during the active phase occurred more in aged mice 28 . To our knowledge, the baseline data reported in this study are the first to show the sleep pattern of 18‐month‐old female C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 65%
“…Of numerous neural networks relevant to the balance of arousal and sleep (Sakurai, 2007;Scammell et al, 2017), the wake-promoting orexinergic neurons are noteworthy as potential targets of KKT, as spinosin, a major ingredient of Ziziphi Semen (ZS), reduces the activation of orexinergic neurons in the lateral hypothalamic area (Zhang et al, 2019). Regarding the influence of aging, older mice exhibited a decrease in rapid eye movement (REM) sleep during the early part of the light phase compared to that in younger mice (Wimmer et al, 2013;Soltani et al, 2019). In this regard, reduced quality of REM sleep in a rat AD model, reflected by a decrease in theta power density during REM sleep, was ameliorated by the Kampo medicine sansoninto, which includes ZS as a major component (Moriyama et al, 2017).…”
Section: Discussionmentioning
confidence: 99%